Association between gender and outcomes of acute burns patients. Issue 1 (1st December 2020) - Perkins, Monica; Abesamis, Gerald M.; Cleland, Heather; Gabbe, Belinda J.; Tracy, Lincoln M.
Abstract : This study explored the association between gender and in‐hospital outcomes of patients with acute burn injuries admitted to burn units in Australia and New Zealand. After adjustment for key differences in case‐mix between men and women, there was an association between gender and in‐hospital mortality and no association between gender and time to death. Our findings indicate that the worse outcomes observed for women are associated with different age and patterns of injury, and provide further information to direct and inform targeted prevention measures for vulnerable populations. Abstract: Background: Burn injuries are a complex and serious public health concern. Where the total body surface area of the burn exceeds 50%, mortality rates as high as 48% have been reported. While the association between gender and burn injury outcomes has been explored, findings are inconsistent. Methods: Adult patients (>15 years) admitted between 1 July 2009 and 30 June 2018 to intensive care units of burn centres that provide specialist burn care in Australia and New Zealand were included. Raw mortality rates were examined and a multivariable Cox proportional hazards regression was used to investigate the association between gender and time to in‐hospital death. Results: There were 2227 eligible burn injury admissions. Men comprised the majority (77.6%). The proportion of women who died in hospital was greater than men and the adjusted odds of in‐hospital mortality were 34% lower in men (odds ratio 0.66; 95% confidence interval (CI) 0.45–0.98). The unadjusted rate of in‐hospital mortality for men was 44% lower than women (hazard ratio 0.56; 95% CI 0.41–0.76). After adjusting for confounders, there was no association between gender and survival time (hazard ratio 0.76; 95% CI 0.54–1.06). Conclusion: After adjustment for key differences in case‐mix between men and women, there was an association between gender and in‐hospital mortality and no association between gender and time to death. Our findings indicate that the worse outcomes observed for women are associated with different age and patterns of injury, and provide further information to direct and inform targeted prevention measures for vulnerable populations.